Transient probabilities for a simple birth-death-immigration process under the influence of total catastrophes - Randall J. Swift (International Journal of Mathematics and Mathematical Sciences, 2001)
The transient probabilities for a simple birth-death-immigration process are considered. Catastrophes occur at a constant rate, and when they occur, reduce the population to size zero.